Hubungan Antara Percaya Diri Dengan Interaksi Sosial Siswa SMK Darul Fikri Kecamatan Pugung Kabupaten Tanggamus - Ria Arianti; Muswardi Rosra; Yohana Oktariana (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The problem in this study is the low social interaction of students. This study aims to determine the relationship between self-confidence and social interaction among students of Darul Fikri Vocational School, Pugung District Tanggamus and Academic Year 2018/2019. The research method used is quantitative correlational. The population of the study was 210 students and the determination using the table to determine the number of samples of Isaac and Michael from a certain population with an error level of 5%, so that is 131 students were taken by simple random sampling technique. Data collection techniques use a scale of confidence and scale of social interaction, data analysis techniques using Product moment correlation. The results showed that there was a significant positive relationship between self-confidence and social interaction with a correlation value of rcount = 0.208 rtable = 0.176 significance level p = 0.05 then Ho was rejected and Ha was accepted. The conclusion of the results of this study is that there is a significant positive relationship between self-confidence and social interaction of students. This means that the higher the confidence the student has, the higher social interaction will be.Permasalahan dalam penelitian ini adalah interaksi sosial siswa rendah. Penelitian ini bertujuan untuk mengetahui hubungan antara percaya diri dengan interaksi sosial pada siswa SMK Darul Fikri Kecamatan Pugung Kabupaten Tanggamus Tahun Ajaran 2018/2019. Metode penelitian yang digunakan bersifat kuantitatif korelasional. Populasi penelitian sebanyak 210 siswa dan penentuan menggunakan tabel penentuan jumlah sampel Isaac dan Michael dari populasi tertentu dengan taraf kesalahan 5%, sehingga jadi ada 131 siswa diambil dengan teknik simple random sampling. Teknik pengumpulan data menggunakan skala percaya diri dan skala interaksi sosial. Teknik analisis data menggunakan korelasi Product moment. Hasil penelitian menunjukan bahwa terdapat hubungan positif yang signifikan antara percaya diri dengan interaksi social dengan nilai korelasi rhitung = 0,208 rtabel = 0,176 taraf signifikasi p=0,05 maka Ho ditolak dan Ha diterima. Kesimpulan hasil penelitian ini adalah terdapat hubungan positif yang signifikan antara percaya diri dengan interaksi social siswa. Artinya semakin tinggi percaya diri yang dimiliki siswa maka akan semakin tinggi interaksi sosialnya.Kata kunci: bimbingan konseling, interaksi social, percaya diri